Problems and Prospects of Small-Scale Industries in India. - Reddy, T. Koti (2008)
The decade of the 1990s was marked by considerable deregulation of the industrial economy through delicensing and dereservations. The problem of sickness in small-scale industries is due to under-utilisation of capacity caused by shortage of working capital, lack of demand, non-availability of raw materials, technological obsolescence, absence of organised market channels, constraint of infrastructural facilities, including power, and deficient managerial and technical skills. With the emergence of World Trade Organisation (WTO) the problems of small-scale units are likely to rise further as they will be increasingly exposed to competition from foreign goods and from multi-national companies. Therefore, it is suggested that the government formulates a comprehensive policy framework to protect the growth and survival of these industries. Policy-makers must appreciate the importance of small-scale industries and empower them to face competition, particularly their Chinese counterparts – both in the domestic and international markets.